Influence of Sources and Mode of Zinc Application on Yield and Uptake of Zinc by Wheat In Aridisols - Gupta, V K; Potalia, B S; Mehla, D S (Annals of Arid Zone, 2016)
Field investigations were carried out to study the effect of sources and mode of Zn application on yield and uptake of Zn by wheat. ZnSO4 produced higher grain yield than ZnO, broadcast method proved superior than placement. Seed coating with 50 g ZnO kg-1 seed, produced higher yield than soil application of 5 kg Zn ha-1 as ZnO applied either’ as broadcast or placement method. Uptake of Zn was more through ZnSO4 at 10 kg Zn ha-1 irrespective 0’ mode of application.